Recruitment of the NineTeen Complex to the activated spliceosome requires AtPRMT5 - Deng, Xian; Lu, Tiancong; Wang, Lulu; Gu, Lianfeng; Sun, Jing; Kong, Xiangfeng; Liu, Chunyan; Cao, Xiaofeng (Proceedings of the National Academy of Sciences - PNAS, 2016)
Protein arginine methylation, catalyzed by protein arginine methyltransferases (PRMTs), is involved in amultitude of biological processes in eukaryotes. Symmetric arginine dimethylation mediated by PRMT5 modulates constitutive and alternative pre-mRNA splicing of diverse genes to regulate normal growth and development in multiple species; however, the underlying molecular mechanism remains largely unknown. A genetic screen for suppressors of an Arabidopsis symmetric arginine dimethyltransferase mutant, atprmt5, identified two gain-of-function alleles of pre-mRNA processing factor 8 gene (prp8-8 and prp8-9), the highly conserved core component of the U5 small nuclear ribonucleoprotein (snRNP) and the spliceosome. These two atprmt5 prp8 double mutants showed suppression of the developmental and splicing alterations of atprmt5 mutants. In atprmt5 mutants, the NineTeen complex failed to be assembled into the U5 snRNP to form an activated spliceosome; this phenotype was restored in the atprmt5 prp8-8 double mutants. We also found that loss of symmetric arginine dimethylation of Sm proteins prevents recruitment of the NineTeen complex and initiation of spliceosome activation. Together, our findings demonstrate that symmetric arginine dimethylation has important functions in spliceosome assembly and activation, and uncover a key molecular mechanism for arginine methylation in pre-mRNA splicing that impacts diverse developmental processes.